2016
DOI: 10.1097/tp.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitors Downregulate HNF-1β and May Affect the Outcome of HNF1B Patients After Renal Transplantation

Abstract: Because HNF1B-related disease is a heterozygous condition, CNIs used to prevent rejection may induce reduced expression of the nonmutated allele of HNF1B leading to a superimposed defect of HNF-1β transcriptional activity. Taking into account the specific risk of posttransplantation diabetes mellitus and liver disorders in HNF1B patients, these findings advocate for in-depth characterization of pathways that regulate HNF1B and plead for considering individually tailored graft management that may include a CNI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…We also added an exploratory analysis on the role of genetic variation in the HNF1b gene on the risk of PTDM. This HNF1b hypothesis was based on reports that (i) patients with HNF1b mutations develop hypomagnesaemia and diabetes mellitus [32,49,50], (ii) patients with HNF1b mutations are more prone to develop PTDM [37], (iii) CNIs down-regulate HNF1b [37] and (iv) SNPs in HNF1b are associated with diabetes mellitus in the general population [33-36, 51, 52]. Although the univariate analysis showed an association between the HNF1b SNP rs752010 G > A and PTDM, significance was lost when adjusting for age and sex ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also added an exploratory analysis on the role of genetic variation in the HNF1b gene on the risk of PTDM. This HNF1b hypothesis was based on reports that (i) patients with HNF1b mutations develop hypomagnesaemia and diabetes mellitus [32,49,50], (ii) patients with HNF1b mutations are more prone to develop PTDM [37], (iii) CNIs down-regulate HNF1b [37] and (iv) SNPs in HNF1b are associated with diabetes mellitus in the general population [33-36, 51, 52]. Although the univariate analysis showed an association between the HNF1b SNP rs752010 G > A and PTDM, significance was lost when adjusting for age and sex ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mutations in the HNF1b gene develop diabetes mellitus and hypomagnesaemia [31,32], and single nucleotide polymorphisms (SNPs) in HNF1b are associated with diabetes mellitus in the general population [33][34][35][36]. Interestingly, a recent study showed that CNIs down-regulate HNF1b, increasing the risk of PTDM 2-to 3-fold in patients with HNF1b mutations [37]. This provided a rationale to explore the role of HNF1b in KTRs receiving tacrolimus.…”
Section: Introductionmentioning
confidence: 99%
“…6 and 13) were known to have had cholestatic episodes, but in both cases, cholestasis developed after renal transplantation and during immunosuppressive treatment with calcineurin inhibitors. In vitro, calcineurin inhibitors downregulate HNF1B gene transcription and translation, and the downregulation of the nonmutated allele has been associated with posttransplantation cholestasis (28). Thus, a pretransplantation diagnosis of HNF1B disease warrants careful follow-up of hepatic and biliary laboratory parameters, which is crucial for an early diagnosis of more severe forms of cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct imaging is rare in patients with HNF1B disease. In endoscopic retrograde cholangiopancreatography (ERCP), one patient had extrahepatic biliary atresia that was confirmed by surgery, and on magnetic resonance imaging (MRI), one patient had slightly dilated intra-and extrahepatic bile ducts (25,28). A few studies provide a limited number of patients who have undergone abdominal MRI (11,28).…”
mentioning
confidence: 99%
“…L'inibitore delle calcineurine (CNI) potrebbe giocare un ruolo particolare nello slatentizzare questa forma di diabete attraverso un'inibizione dose-dipendente della trascrizione dell'allele sano di HNF1β. Questi dati, se confermati, potrebbero fornire un'indicazione ad adottare protocolli di minimizzazione del CNI in questi pazienti (13).…”
Section: Tabella I -Principali Caratteristiche Delle Adtkdunclassified